Motherhood in precarious times (DEMETER Press, 2018)
Parenting brings countless hopes and worries. But when external factors create fear and cast a shadow long and deep across motherhood, what happens to the act of mothering? Through personal and academic essays and poetry from Canada, the United States, and Palestine, these authors explore what it means to mother through times of struggle, uncertainty, danger, and change. From doctors and professors, to writers and environmentalists, women of different ages, cultures, and backgrounds share their insights and perspectives on what it is to mother when life, society, and the very future of those yo.